2021
DOI: 10.48185/she.v2i2.377
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in the Application of Alternative Delivery Mode (ADM) Learning Resources during the Pandemic Period

Abstract: This study reflected the experiences and perspectives of Learning Resource Coordinators during the COVID-19 pandemic in the application of the Alternative Delivery Mode (ADM) Learning Resources in the Schools Division Office, Central Luzon, Philippines. The study employed a narrative-inquiry approach to gather pertinent experiences from a group of participants. The participants were 10 Learning Resource Coordinators selected using a cluster sampling technique. The proponent used a research-made questionnaire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, the school administration also encourages the teachers to attend training to equip them with the necessary knowledge and skills in instructional technology. In a related study by Jimenez (2021), the researcher revealed the different experiences and challenges that teachers met and the different solutions they made to implement the alternative delivery model.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the school administration also encourages the teachers to attend training to equip them with the necessary knowledge and skills in instructional technology. In a related study by Jimenez (2021), the researcher revealed the different experiences and challenges that teachers met and the different solutions they made to implement the alternative delivery model.…”
Section: Introductionmentioning
confidence: 99%
“…The previous school years' learning modalities [13] have adjusted to a new paradigm shift in the curriculum and implementation. The enhanced curriculum is worth waiting while the combination of teaching modalities is well exciting.…”
Section: Introductionmentioning
confidence: 99%